Coating two-dimensional MoS2 with polymer creates a corrosive non-uniform interface. (December 2018) - Thi, Quoc; Kim, Hyun; Zhao, Jiong; Ly, Thuc
Abstract Two-dimensional (2D) materials and soft materials are both susceptible to mechanical instabilities, such as buckling, wrinkling, folding and creasing, especially when located on surfaces. Here, we report that weak van der Waals interactions cause the interface between 2D molybdenum disulphide (MoS2 ) and a soft poly(methyl methacrylate) coating to demonstrate mechanical instability and delamination. The resulting non-uniform and buckled interface greatly hampers the ability of the coating to protect the MoS2 substrate. Also, the corrosion rate of 2D MoS2 and quench rate of intrinsic luminescence in 2D MoS2 were significantly accelerated by the soft coating. Owing to the formation of corrosive cavities at the interface, the geometry and size of the flakes became the dominating factor, and a critical size of 2D flakes for such interfacial instability was determined based on elasticity theory. Such hazardous corrosion in a 2D material caused by a soft coating raises concern for their use in electronic packaging, and for the processing of van der Waals-layered materials for future applications. Corrosion: hampered protection capabilities of polymer coatings on 2D materials The interface between a 2D material and a soft polymer coating may suffer from mechanical instabilities and delamination. A team led by Thuc Hue Ly at City University of Hong Kong investigated the role of soft coating layers like Poly methyl methacrylate (PMMA) in the protection of atomically thin transition metal dichalcogenides. A combination of experimental techniques including atomic force microscopy, photoluminescence and Raman spectroscopy indicated formation of corrosive cavities at the interface between PMMA and the chalcogenide monolayers. The enhanced corrosion behaviour of 2D materials in the presence of soft polymer coatings resembles the corrosion under insulation (CUI) phenomenon known in industry. As the geometry and size of flakes dominate the corrosion rate, a rational design of such interfaces should be employed to avoid CUI events.